The Trinity and the Rainbow: Colour in Gregory of Nyssa’s Letter to Peter of Sebaste - Haykin, Michael A. G. (Reformed theological review, 2025)
Letter 38, which is normally located in the corpus of Basil of Caesarea’s correspondence but is actually written by his brother Gregory of Nyssa, is a profound reflection upon the vital necessity of distinguishing between the terms person and being in language about the divine Trinity. As an aid to thinking about this distinction, Gregory employs the analogy of the rainbow. While the rainbow had a positive meaning in the Judaeo-Christian tradition, it had very different connotations in pagan Graeco-Roman culture. Drawing, in part, upon Aristotelian thought about the rainbow’s nature, Gregory not only aids Trinitarian reflection but also provides this natural phenomenon with new meaning for his Graeco-Roman context.